Emergence Of Museums And Significance Today - Kasimova Nilufar; Sattorova Sarvinoz; Mamatov Ilyos; Mamatqulov Rashid; Ergashev Madaminjon (Journal of Advanced Zoology, 2023)
Museums are the main means of delivering information about the periods of human development and unique masterpieces of each field to the future generation. Museums first appeared in the form of collections, and these collections were shown to the public with samples of rare works and items that were eaten by wealthy people among the population. Famous museums in the world have been built slowly.